DEVELOPING READING COMPREHENSION SKILLS IN 5TH-GRADE STUDENTS: PSYCHOLINGUISTIC FOUNDATIONS AND METHODOLOGICAL RECOMMENDATIONS - Nosirova Kamola Xusniddin qizi (Modern American Journals, 2025)
The article examines the development of reading comprehension in 5th-grade learners from psychophysiological and psycholinguistic perspectives. It relates the transitional stage of early adolescence (ages 10–11) to instructional content and methods, outlining multistage models of comprehension – from graphic decoding to intertextual comparison. Practical guidelines are offered: age-appropriate text selection, visual scaffolds (pictures/diagrams), clear and unambiguous language, memory exercises, and supportive classroom climate. The paper argues for individualized instruction, motivation-enhancing strategies, and creative tasks to strengthen students’ oral and written expression as well as their ability to transfer textual information to real-life situations.
Keywords: Reading comprehension, grade 5, psycholinguistics, early adolescence, cognitive processes, individualized instruction, levels of text processing, didactic tasks, memory training, learner motivation.